2012
DOI: 10.1037/a0025586
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-dependent modulation of serotonergic markers in auditory areas of a seasonally breeding songbird.

Abstract: Because no organism lives in an unchanging environment, sensory processes must remain plastic so that in any context, they emphasize the most relevant signals. As the behavioral relevance of sociosexual signals changes along with reproductive state, the perception of those signals is altered by reproductive hormones such as estradiol (E2). We showed previously that in white-throated sparrows, immediate early gene responses in the auditory pathway of females are selective for conspecific male song only when pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 113 publications
(216 reference statements)
2
50
1
Order By: Relevance
“…It is also consistent with the finding that estradiol increases the density of serotonin receptors in the central auditory system of birds (Matragrano, 2012) and the finding that serotonin increases response latency in some IC neurons in the bat (Hurley and Pollak, 2005). It appears that a decrease in speed and temporal precision of responses to sound during pregnancy may be a characteristic of female warm-blooded vertebrates.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is also consistent with the finding that estradiol increases the density of serotonin receptors in the central auditory system of birds (Matragrano, 2012) and the finding that serotonin increases response latency in some IC neurons in the bat (Hurley and Pollak, 2005). It appears that a decrease in speed and temporal precision of responses to sound during pregnancy may be a characteristic of female warm-blooded vertebrates.…”
Section: Discussionsupporting
confidence: 90%
“…Female white-throated sparrows given estradiol (E2) and exposed to conspecific male song, show increased density of serotonin receptors on fibers that innervate the auditory system, suggesting that E2 affects the auditory system via serotonin. (Matragrano et al, 2012). Auditory brainstem response (ABR) studies in white-crowned sparrows have paradoxically shown increased thresholds and response latencies in both sexes when in breeding condition (Caras et al, 2010) but increased precision of spike timing in female sparrows given estrogen (Caras et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Direct manipulation of estrous hormones also influences the serotonergic system in multiple animal models. In seasonal breeders like female white-throated sparrows, inducing breeding condition with estradiol causes upregulation of the serotonergic system in different auditory areas, increasing the density of serotonergic fibers and increasing 5-HIAA levels in response to playback of speciesspecific songs (Matragrano et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Brain serotonin is also sensitive to internal influences such as reproductive state and sex (Maswood et al, 1999;Jitsuki et al, 2009). Estrogen levels, which fluctuate across female reproductive state and differ between the sexes, influence serotonergic function in sensory brain regions (Rubinow et al, 1998;Abizaid et al, 2005;Matragrano et al, 2012). Membrane-bound serotonin receptors decrease and binding affinity of serotonin to receptors decreases with increased estrogen levels, and during proestrus and estrus in rats (Biegon et al, 1980;Mize and Alper, 2000).…”
Section: Research Articlementioning
confidence: 99%
“…Collectively, these findings strongly implicate NE in the estrogenic modulation of songbird auditory function. Future studies are needed to determine the precise functional role other monoamines play in this process, as a separate study similarly implicated serotonin in mediating the effects of E 2 (Matragrano et al, 2012a). Additionally, it is worth noting that the rodent LoC is also sensitive to estrogens (Helena et al, 2006; Serova et al, 2004), which suggests that these findings may have important implications for non-avian species.…”
Section: What Are the Molecular Mechanisms?mentioning
confidence: 99%